Evaluating the performance of the twin tunnel complex in soft soil subjected to horizontal ground shaking - Naseem, Ahsan; Ansari, Wajahat Sammer; Kashif, Muhammad; Sadiq, Shamsher; Schotte, Ken; De Backer, Hans (Frontiers in Environmental Science, 2023)
Tunnel construction in soft soil necessitates a thorough evaluation of soil behavior, embedment depth, ground heaves, and tunnel distortions, especially in earthquake-prone areas. This study presents a numerical parametric investigation of an unconventional tunnel complex formed by combining the closely located twin tunnels. The complex is subjected to varying horizontal ground vibrations, and the influence of lining thickness, embedment depth, and interface conditions on seismic-induced thrusts, shear forces, bending moments, tunnel distortions, and ground heaves is assessed. The applicability of analytical solutions from existing literature for singular tunnels is examined through detailed analyses of different embedment ratios. The study reveals that increased tunnel flexural rigidity leads to higher seismic-induced bending moments in the tunnel complex. Comparing full-slip and no-slip interface conditions, the former exhibits reduced overall tunnel distortions. Furthermore, a comparison is made with a conventional-shaped rectangular tunnel complex. The results indicate that the twin tunnel complex behaves more rigidly under a constant embedment ratio and input motion amplitude. It also results in lower ground heaves and suffers lesser induced lining forces during seismic events, making it a superior performer in comparison. Overall, this research provides valuable insights into the behavior of twin tunnel complexes in soft soil under seismic conditions, showcasing their advantages over conventional shaped tunnels in terms of tunnel distortions, ground heaves, and overall structural response.